Nanomaterials reshape the pulmonary mechanical microenvironment: novel therapeutic strategies for respiratory diseases - Li-zhen Chen; Li-zhen Chen; Peng-fei Zheng; Qi Cai; Run-nan Chen (Frontiers in Bioengineering and Biotechnology)
Respiratory diseases, including chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), and lung cancer, exhibit elevated death rates and pathological intricacy, requiring advancements that surpass the constraints of traditional therapies. This study comprehensively outlines the novel applications of nanomaterials in respiratory medicine by accurately modulating the pulmonary mechanical microenvironment, encompassing alveolar surface tension, extracellular matrix rigidity, and the immune-fibroblast interaction network. The precise delivery, stimuli-responsive characteristics, and biomimetic design of nanomaterials markedly improve drug concentration at the lesion site and mitigate fibrosis, inflammation, and malignant tumor advancement by disrupting mechanical signaling pathways. The study clarifies their multifaceted benefits in treating COPD, IPF, and lung cancer, including decreased systemic toxicity and improved spatiotemporal control. Nonetheless, clinical translation continues to encounter obstacles, including impediments in large-scale production, inadequate compatibility with breathing devices, and disputes concerning long-term biosafety. In the future, the amalgamation of precision medicine, adaptive smart materials, and multi-omics artificial intelligence technologies will facilitate the development of individualized diagnostic and therapeutic systems, establishing a novel paradigm for the proactive management of respiratory disorders. This review offers essential theoretical foundations and technical approaches for the practical application of nanomaterials and the enhancement of therapeutic techniques in respiratory medicine.